Application of foliar sprays containing copper, zinc and boron to mature clonal tea (Camellia sinensis) : effect on yield and quality - Taylor, Nicolette Jane (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2012.